Role of environmental impact assessment act in achieving sustainable cities and communities in Nigeria (2018)
"Nigeria is a country endowed with cities and communities of great resources. Making these cities and communities sustainable in all ramifications, the environmental impact assessment (EIA) act 2004 is one of the legal instruments that has to be adhered to strictly. Initial moves of stakeholders on world concerns on the utilising environmental resources justly called for international conferences from World Summits from Stockholm to Nairobi to Rio and to Johannesburg. These international conferences have set paces for most nations of the world on the need to adopt and implement the concepts and policies of sustainable development. Nigeria was among States in the United Nations World submit where seventeen (17) sustainable development Goals were adopted in September, 2015 in New York, United States of America (USA). These goals are targeted towards eradicating unpleasant social, economic and environmental problems in all nations of the world by year 2030. Goal eleven (11) of the Sustainable Development Goals precisely provides for sustainable cities and communities. This article considers the essence of the Nigerian Environmental Impact Assessment Act to achieving goal eleven of among the seventeen SDGs. The articles considers the conceptual frameworks of both Environmental Impact Assessment and Sustainable development as well as the international frameworks on these concepts. This article further considers the development of EIA and SDGs in Nigeria together with peculiar nature of the country and its cities and community. The provisions of the EIA and other related legal frameworks are examined to harness their essence with achieving the sustainable cities and communities. Impediments to enforcing the provisions of the EIA towards achieving sustainable cities and communities are considered. The article also juxtapose EIA in three jurisdictions with Nigeria’s efforts to implement the EIA provisions with aims of achieving sustainable cities and communities. This articles concludes with observations and recommendations that will enhance enforcement of EIA towards achieving sustainable cities and communities in Nigeria"